La atención a los indicadores de dislexia y su incidencia en el desarrollo de las habilidades de la lecto-escritura de los niños de 7mo grado de escuela fiscal de educación básica Mayor Ignacio Viteri Mosquera - Cueva Carrillo, Sandra Judith (2018)
The presented research work is titled "attention to the indicators of dyslexia and its impact on the development of the skills of reading and writing of children in 7th. Grade school education basic "Major Ignacio Viteri Mosquera" Prosecutor. It arises from the need to identify the indicators of dyslexia, analyse the specific situation of the Centre and propose a comprehensive plan active that you commit to parents and teachers in the solution of this problem. The research problem focuses on how you affect the indicators of dyslexia Diagnostics classes at school. Used the methodology research takes a psychological approach and methodology to a large extent is descriptive, allowing you to confirm the fact that investigates and address educational problems in an important way in the different fields of the Psychology and pedagogy of the studied educational level……….